Assessment of lifestyle of American football players training in Poland - Dominik Olejniczak; Justyna Leciejewska; Urszula Religioni; Wojciech Boratyński; Agnieszka Barańska; Bartłomiej Drop (Kazimierz Wielki University, 2018)
Introduction In recent years, American football has gained a wide range of supporters in Poland and the number of people regularly training is growing. With the increasing curiosity about American football, many questions are asked about the sport and the people training it, especially regarding the lifestyle of players. Aim The aim of the study was to determine the lifestyle of American football players with particular emphasis on the assessment of health behavior and health risk determinants. Material and method The study authors used a questionnaire in an electronic form sent out to the leaders of American football teams in Poland. The study included 400 people - members of sports clubs. The statistical method was the Chi square test. The adopted level of significance was p